Blockchain-Based Skill and Employment Verification: Challenges and Strategies for Executive Hiring in Dubai’s FinTech Industry - Gollapalli, Hulda (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation investigates the impact of blockchain technology on the executive hiring processes within Dubai's FinTech sector, focusing on skill and employment verification, fraud reduction, adoption willingness, and the effects on time and cost efficiency. The traditional executive hiring process faces challenges such as fraudulent credentials, verification delays, and high recruitment costs. With its decentralized and immutable nature, blockchain offers a potential solution to these issues by ensuring secure, accurate, and efficient verification. The research employs a mixed-methods approach, combining quantitative surveys with HR professionals, hiring managers, and IT specialists from various FinTech organizations in Dubai. The survey examines respondents' perceptions of blockchain's effectiveness in verifying credentials, reducing fraudulent claims, and improving recruitment efficiency. Additionally, the study explores organizational readiness to adopt blockchain technology and its potential impact on operational costs and time. The findings reveal that blockchain significantly improves verification accuracy by reducing human error and preventing fraud. The decentralized verification system was identified as an effective tool for mitigating fraudulent claims in executive hiring. Blockchain also positively influenced time and cost efficiency, with respondents reporting faster verification processes and reduced recruitment costs post-adoption. However, barriers such as resistance to new methods and concerns about implementation costs were identified, potentially hindering widespread adoption. In conclusion, blockchain technology holds significant potential to enhance the executive hiring process in Dubai's FinTech sector, particularly regarding verification accuracy, fraud prevention, and operational efficiency. Addressing resistance to change, reducing implementation costs, and providing adequate training are essential for successful adoption. The study suggests further research into long-term blockchain adoption and its impact across different industries. Keywords: Blockchain, Executive Recruitment, Fraud Reduction, Skill Verification, Time Efficiency, Cost Efficiency, FinTech, Adoption Barriers.